Roles performed by bank branch managers in Malaysia - Ng, Siew Imm; Tee, Keng Kok; Lau, Yeng Wai (Wydawnictwo Politechniki Śląskiej, 2010)
This paper discusses managerial roles performed by bank branch managers in Malaysia basing on Mintzberg's model. In-depth understanding of managerial roles performed is significant to organization in at least two ways: improve managerial recruitment effectiveness and identify suitable training programs for existing managers. Data was collected from 143 bank branch managers across Peninsular Malaysia via interview survey. There were at least four implications worth noting here. First, Mintzberg's (1971) framework was indeed applicable in Malaysia although it has been developed more than 38 years ago. Second, there were indeed changes in role rankings, suggesting role emphasis changes over time. Third, roles more emphasized by today’s managers were interpersonal and informational roles while role less emphasized was decisional role. Fourth, male and female managers were found to perform all 10 roles in the same extent. Practical implications were then discussed.